Tree-ring width reveals evaporation signals in semi-arid regions of the United States - Lingze Xu; Hongkai Gao; Wenling An; Zheng Duan (Environmental Research Communications)
Tree-ring width chronologies have been widely used to reconstruct past hydroclimate variability, including precipitation, temperature, and streamflow. However, their relationship with evaporation—a key component of ecosystem water use—remains poorly quantified and understood. Here, we systematically evaluate the relationship between tree-ring width and observed hydrometeorological variables across 25 catchments within the contiguous United States. We find that in 9 of 19 catchments, tree-ring width exhibits the strongest correlation with evaporation from January to September ( $E$ ), evaporation from May to August ( ${E}_{5-8}$ ) or transpiration ( ${E}_{T}$ ), rather than precipitation or streamflow. These catchments are predominantly located in semi-arid regions and the southern western United States, where root zone moisture limitation strongly constrains tree growth. Our results demonstrate that tree-ring width can serve as a robust proxy for catchment-scale actual evaporation, particularly in water-limited ecosystems.